Labor-management Relations in Emerging Economies and Developing Countries - Frank M. Horwitz; Fang Lee Cooke (Global Labor Organization (GLO), 2021)
Adopting a largely institutional theoretical perspective, this chapter focuses on emerging and developing economies in Africa and Asia, including labor-management relations in South Africa and other jurisdictions in both Africa and Asia. The aim is to assess the effects of changes in the labor markets and regulatory institutions pertaining to employment relations. Whilst other theoretical lenses such as socio-cultural and cross-cultural management and postcolonial approaches are important, this chapter critically evaluates the institutional effects relating to changes in the nature of work and the effects of external factors on market and employment relations institutions. Providing a definitional overview, this chapter discusses empirical evidence on determinants and outcomes of institutions. Though referring to other regions such as Latin America, in order to narrow the scope of analysis, the analysis focuses on two major emerging and developing economic regions, namely Asia and Africa. It includes a discussion of the Africa-Asia nexus or Sino-Africa interface in labor-management relations. Labor market institutions, their relative strengths and weaknesses, trade unions and collective bargaining, inequality and informalization of employment practices, are discussed.
Keywords: 330